2017
DOI: 10.5194/amt-10-2377-2017
|View full text |Cite
|
Sign up to set email alerts
|

A closed-chamber method to measure greenhouse gas fluxes from dry aquatic sediments

Abstract: Abstract. Recent research indicates that greenhouse gas (GHG) emissions from dry aquatic sediments are a relevant process in the freshwater carbon cycle. However, fluxes are difficult to measure because of the often rocky substrate and the dynamic nature of the habitat. Here we tested the performance of different materials to seal a closed chamber to stony ground both in laboratory and field experiments. Using on-site material consistently resulted in elevated fluxes. The artefact was caused both by outgassing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…When intrusion of the chamber to the ground was prevented (e.g. by a stony surface), the chamber was sealed to the ground using clay 50 . Chamber placement was restricted to plots with bare ground and sampling of vegetated surface was avoided.…”
Section: Methodsmentioning
confidence: 99%
“…When intrusion of the chamber to the ground was prevented (e.g. by a stony surface), the chamber was sealed to the ground using clay 50 . Chamber placement was restricted to plots with bare ground and sampling of vegetated surface was avoided.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of CO 2 in the chamber was continuously monitored by a portable GHG analyser (microportable GHG analyser, LosGatos Research, USA). Previous tests had shown that our system gave reliable flux data without using preinstalled collars (Lesmeister & Koschorreck, 2017) and that the pump of the gas analyser created enough air mixing in the chamber that we could do without a fan (Koschorreck, unpublished).…”
Section: Co 2 Flux Measurementsmentioning
confidence: 99%
“…This intermediate scale heterogeneity prevents the use of spatially integrating methods such as eddy covariance to measure CO 2 emissions as the method requires a larger homogenous footprint area (Aubinet, Vesala, & Papale, 2012). The only available method to measure CO 2 emissions in these heterogeneous areas is discrete point measurements using closed chambers (e.g., Bolpagni et al, 2017;Lesmeister & Koschorreck, 2017). Chamber-based CO 2 measurements proved to vary between land cover and are affected by sediment texture, sediment organic matter, sediment moisture, sediment temperature and chlorophyll a (Gallo et al, 2014;Gómez-Gener et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The chambers were opaque to minimize temperature change. We used clay around the exterior of the chambers to avoid gas leakage (Lesmeister and Koschorreck 2017). Soil temperature and conductivity were determined using a conductivity meter (Akrom KR31).…”
Section: Co 2 Flux From Drawdown Areasmentioning
confidence: 99%